Pengaruh Pupuk Organik Cair Berbasis Bahan Lokal Terhadap Pertumbuhan dan Hasil Jagung di Tanah Regosol Bantul: The Effect of Liquid Organic Fertilizer Based on Local Ingredients on the Growth and Yield of Corn in Regosol Soil of Bantul - Eko Srihartanto; Soeharsono Soeharsono; Agung Iswadi (Agrocentrum, 2023)
Liquid organic fertilizer (LOF) based on local ingredients is expected to increase corn productivity in regosol soil. The purpose of this study was to find out the best dose to increase the growth and yield of corn in Bantul regosol soil. The methodology used a complete randomized block design with 6 treatments (control, very low POC dose of 5 ml/l, Low 7.5 ml/l, Moderate 10 ml/l, High 12.5 ml/l and Very High 15 ml/l) each of which was repeated 4 times so that there were 24 treatments. Observation of vegetative - generative growth and yield of corn plants. The collected data were processed and analyzed statistically using variance (ANOVA/Analysis Of Variance) and followed by a follow-up test at the 5% level of significance to see differences between treatments. The results showed that the best Megarhizo POC dose was 7.5 ml/l, this was indicated by the optimum plant growth and the highest maize yield of 10.26 tons/ha compared to other treatments.